A Study on Branded Men's Wear - Narang, Ritu (Indian Journal of Marketing, 2006)
The apparel industry is one of India's largest foreign exchange earners, accounting for 12% of the country's total exports. Garment manufacturing is one of the most fragmented sectors of the Indian textile industry. The garment industry comprises of manufacturers of ready-made garments for either the domestic or export markets or, in certain cases, both. The constituents of this segment are very diverse in terms of their size, production facility, the type of apparel manufactured, the quality of output, fabric requirement, price sensitivity etc. The segment is extremely fragmented, with an estimated 27,000 domestic manufacturers, 48,000 fabricators (job contractors) and around 1000 manufacturer-exporters. This is an industry with no visibility of data in an organized sense. So, the figures quoted are more of industry estimates rather than of any organized research. The apparel segment on a whole is estimated to be Rs. 40,000 crores (Rs 400 billion) and of that the branded apparel segment is estimated to be Rs 9,000 crores (Rs 90 billion).